The role of ubuntu in conflict resolution : the case of the Malamulela and Vuwani conflict in Vhembe District, Limpopo Province - Risimati, Tlharihani Michael (My University, 2023)
This thesis explores the role of Ubuntu in conflict resolution in the communities of Malamulele and Vuwani, located in Vhembe District of Limpopo Province, South Africa. Despite the decline in the current South African liberal democracy and the challenges that it faces with respect to its restoration, Ubuntu remains pivotal to conflict resolution. Nevertheless, there is hope for the restoration of Ubuntu on condition of a proper and diligent implementation of the tentative Ubuntu Conflict Resolution Model (UCRM), outlined in this study. The study utilised qualitative research methods to explore the role of Ubuntu in conflict resolution in the case of the Malamulele and Vuwani conflict. As a decolonised anthropological study, it examined African human behaviours and cultures with a view to comprehending the society. Based on primary data collected from interviews, the role of Ubuntu in the conflict was uncovered. The entire study utilised Ubuntu as a theoretical framework to analyse the data provided by the participants. The study found that Ubuntu remains a useful tool to unify, amend, heal, reconcile, and maintain broken relationships, if it is restored adequately. However, the study identified a decline of Ubuntu among the Malamulele and Vuwani community members, but the hope is there for Ubuntu to thrive again since there are some members of the communities who still hold Ubuntu and if steps suggested in this study could be taken into consideration. It was discovered that Ubuntu is an independent variable, and fosters quality traditional, family, educational, religious and political leadership. Quality education is enhanced by Ubuntu as its philosophical foundation. In fact, Ubuntu requires environments that are conducive to its own survival; without these environments it may struggle to exist. The study suggested a tentative UCRM; a model that may be used in the communities of Malamulele and Vuwani to resolve conflict on a shortand long-term, bases. While some of the cultural practices of traditional leadership families such as human sacrifice are controversial and unacceptable considering the values of Ubuntu and their roles as cultural custodians of social justice and human rights, the study recommended further descriptive investigation which will look at Ubuntu in traditional leadership practices in contemporary South Africa. Nevertheless, the study has shown that Ubuntu has a place and role to play in the new liberal democratic society since the hope for its restoration is still there.
Thesis (Ph.D. (Anthropology)) -- University of Limpopo, 2023
Keywords: Ubuntu; Conflict resolution; Ethnic identity; Violence; Community protest; Solidarity; Ubuntu (Philosophy); Conflict management; Ethnicity; Conflict management